International clinical guidelines for the management of phosphomannomutase 2‐congenital disorders of glycosylation: Diagnosis, treatment and follow up. Issue 1 (11th February 2019) - Altassan, Ruqaiah; Péanne, Romain; Jaeken, Jaak; Barone, Rita; Bidet, Muad; Borgel, Delphine; Brasil, Sandra; Cassiman, David; Cechova, Anna; Coman, David; Corral, Javier; Correia, Joana; et al.
Abstract: Phosphomannomutase 2 (PMM2‐CDG) is the most common congenital disorder of N‐glycosylation and is caused by a deficient PMM2 activity. The clinical presentation and the onset of PMM2‐CDG vary among affected individuals ranging from a severe antenatal presentation with multisystem involvement to mild adulthood presentation limited to minor neurological involvement. Management of affected patients requires a multidisciplinary approach. In this article, a systematic review of the literature on PMM2‐CDG was conducted by a group of international experts in different aspects of CDG. Our managment guidelines were initiated based on the available evidence‐based data and experts' opinions. This guideline mainly addresses the clinical evaluation of each system/organ involved in PMM2‐CDG, and the recommended management approach. It is the first systematic review of current practices in PMM2‐CDG and the first guidelines aiming at establishing a practical approach to the recognition, diagnosis and management of PMM2‐CDG patients.